2016
DOI: 10.1161/circulationaha.116.022498
|View full text |Cite
|
Sign up to set email alerts
|

Letter by Murakami et al Regarding Article, “Surgically Constructed Double-Outlet Right Ventricle”

Abstract: We read with great interest the article by Egbe and colleagues, 1 which reported a new operation with the homograft conduit from the right ventricle (RV) to the right pulmonary artery (PA) for the patient with occlusion of the right PA. The operation is excellent; however, the description of the RV deserves comment.The outlet belongs to the ventricle. Anatomically, the RV can be divided into inlet, trabecular, and outlet regions.2 Therefore, the double-outlet ventricle has 2 outlet portions, usually to the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In today's electron devices having nanometer-scale dimensions, there are many unignorable issues that make the characteristics of electron devices manufactured in the same chip different from each other, such as random dopant fluctuation (RDF), [1][2][3][4][5][6][7][8][9] interface roughness, 10,11) line edge roughness, [12][13][14][15][16] the grain boundaries of gate dielectric materials, 17) and so on. Among them, RDF has been extensively studied for several decades because it is the most significant in device modeling as long as electron devices use PN junctions, since it is related to the validation of the DD model that device scaling has assumed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's electron devices having nanometer-scale dimensions, there are many unignorable issues that make the characteristics of electron devices manufactured in the same chip different from each other, such as random dopant fluctuation (RDF), [1][2][3][4][5][6][7][8][9] interface roughness, 10,11) line edge roughness, [12][13][14][15][16] the grain boundaries of gate dielectric materials, 17) and so on. Among them, RDF has been extensively studied for several decades because it is the most significant in device modeling as long as electron devices use PN junctions, since it is related to the validation of the DD model that device scaling has assumed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tsunomura et al reported measurements showing that one million transistors simultaneously manufactured have non-negligible fluctuation in threshold voltages (about 0.5 V), 19) which may be due to RDF as well as to the abovementioned manufacturing variation. [10][11][12][13][14][15][16][17] Shin et al performed a simulation of 200 samples and showed that threshold voltage fluctuation is typically in the order of several tens of millivolts. 20) These fluctuations may be understandable if two transistors having different spatial distributions of dopant ions result in two different threshold voltages.…”
Section: Introductionmentioning
confidence: 99%